The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1016/j.ijom.2004.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The use of SPECT to evaluate growth cessation of the mandible in unilateral condylar hyperplasia

Abstract: In unilateral condylar hyperplasia, for surgical intervention to be effective, the status of condylar bone growth has to be assessed correctly. Previously this assessment relied on serial clinical observations. This study aimed to evaluate the MDP-SPECT method of assessing condylar growth in unilateral condylar hyperplasia. Twenty-six MDP-SPECT of the mandible had been performed; 21 were diagnosed as condylar hyperplasia and five as non-mandibular disease. Three isotope parameters: isotope counts, pixel counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 17 publications
1
42
0
6
Order By: Relevance
“…The planar bone scanning technique was used in 8 studies 1,3,7-9,11,25,26 , SPECT scanning in 1 study 22 and a combination in 4 studies 2,12,21,29 . In 2 studies 18,30 , the scanning technique used was not specified.…”
Section: Bone Scintigraphic Studies Of Patients With Facial Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…The planar bone scanning technique was used in 8 studies 1,3,7-9,11,25,26 , SPECT scanning in 1 study 22 and a combination in 4 studies 2,12,21,29 . In 2 studies 18,30 , the scanning technique used was not specified.…”
Section: Bone Scintigraphic Studies Of Patients With Facial Asymmetrymentioning
confidence: 99%
“…Seven studies 1,9,11,12,22,25,29 presented results in enough detail (i.e. number of patients with presence/absence of UCH and number of abnormal and normal bone scan results) to calculate the index test characteristics (i.e.…”
Section: Bone Scintigraphic Studies Of Patients With Facial Asymmetrymentioning
confidence: 99%
“…Previous studies have, however, relied only on planar images [15,16]. SPECT (Single Photon Emission Computed Tomography) [17,18] has been used with quantitative assessments of one mandibular condyle to clivus or lumbar spine, but when one condyle is compared with the other, it is more sensitive and accurate in detecting abnormal activity. A relative percentage uptake of 55% or more in the affected condyle is considered to be abnormal, and this has been validated by comparison with an age-matched control group.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This procedure is widely used in the evaluation of patient with suspected UCH. Literature based on control studies indicate that normal individuals or patients without progressive facial asymmetry show a difference in radiotracer uptake values between the left and right condylar regions less than 10%, whereas a difference greater than 10% is strongly suggestive of active UCH [12]. Nevertheless, a systematic review of the literature by Saridin et al reported a large variability between studies from different centers performing SPECT scan [5].…”
Section: Discussionmentioning
confidence: 99%